Managing Multiple Roles: Communication and Role Conflict Among Indonesian Postgraduate Women - Shela Kusumaningtyas; Wawan Hadinata; Nur Iman; Yunati Alinda; Adinda Aulia Nurhaliza; Leoni Nindyasari (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine how Indonesian women who simultaneously fulfill the roles of wife, mother, professional worker, and postgraduate student manage multiple role conflicts through interpersonal and intrapersonal communication. Using a qualitative case study design, six postgraduate students from the University of Indonesia were purposively selected as participants. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings indicate three major themes. First, interpersonal communication with spouses, family members, colleagues, and academic peers facilitates mutual understanding and role negotiation. Second, intrapersonal communication, such as self-reflection and emotional regulation, helps participants cope with guilt, fatigue, and academic pressure. Third, social support networks emerging from effective communication enable participants to sustain their motivation and maintain balance across domestic, professional, and academic domains. These findings highlight that communication functions as a practical strategy for managing multiple identities and mitigating the effects of role conflict. The study offers implications for developing gender-sensitive communication training and institutional support systems to empower women in higher education and the workplace.